How do free public transport policies impact economic and environmental outcomes? Evidence from Brazil - Rodrigues, Mateus Santos (2024)
Climate change poses a significant challenge for the current generation, with implications extending beyond environmental concerns to various economic variables. In this context, national and supranational institutions emphasize the need to reduce greenhouse gas emissions, prompting the development of climate mitigation policies. This study focuses on exploring the impacts of a specific policy implemented by several Brazilian municipalities: the implementation of fare-free public transportation. Employing a difference-in-differences approach with staggered treatment adoption, we find that fare-free transit leads to a reduction in greenhouse gas emissions while simultaneously boosting local employment levels by reducing commuting costs. These findings support the idea that such policies can induce absolute decoupling – defined as a scenario where economic activity grows while greenhouse gas emissions decrease or remain stable – and sustainable growth, at least at the local level. Further examination of the mechanisms behind these results indicates that individuals are not abandoning car usage due to these policies, but rather, there is a shift in the composition of employment within local economies.